Pemberdayaan Masyarakat Desa Cilolohan: Optimalisasi Potensi Lokal melalui Pendekatan Edukatif dan Partisipatif - Tri Agustini Solihati; Raka Saepul Akbar; Natasha Deva Yuniar; Shakira Daffa; Aubin Raivy Pramorda; Agus Ihsan (Journal of Empowerment Community, 2026)
Community Service Program (KKN) is a form of student community service aimed at applying knowledge and technology outside the campus while serving as a learning medium for students to understand social realities. The KKN program in Cilolohan Village, Tanjungjaya District, Tasikmalaya Regency, was conducted against the background that the village has great potential in agriculture, handicrafts, and tourism, yet still faces various challenges such as limited access to clean water, low education levels, and suboptimal management of local potential. The objective of this activity was to empower the community through educational, participatory, and sustainable approaches. The implementation methods included participatory observation, focused group discussions (FGD), mentoring and training, as well as potential and problem mapping. The results of the KKN program showed an increase in community awareness in the fields of education, health, and the environment; strengthening of local MSMEs through digital marketing assistance; and improved community preparedness in disaster mitigation. It is concluded that KKN has positively contributed to optimizing local potential and strengthening synergy among students, the community, and village government, withrecommendations for sustainable development in the future.